Adolescence: A Window of Opportunity for Positive Change in Mental Health - Wekerle, Christine; Waechter, Randall L.; Leung, Eman; Leonard, Monika (First Peoples Child & Family Review, 2007)
Adolescence is a period of development characterized by risk-taking, sensation-seeking, emotionally-inﬂuenced and independence-seeking behaviours. There is a move away from family and towards the social inﬂuences of peer groups. Emotionally-driven behaviours may override adolescents’ higher cognitive functioning during this time. Especially vulnerable are youth who have been the victim of high-impact trauma or chronic abuse and neglect. Speciﬁcally, the posttraumatic stress symptomatology that is often associated with experiences of abuse and neglect may impair the ability of youth to cope during this developmental period. This is where intervention by community workers may be used to support teens with a history of maltreatment, as they develop from children to adolescents and, ﬁnally, to adults. Part of such intervention includes violence prevention in families and in teen dating relationships, as well as directly addressing posttraumatic stress disorder symptomatology. This critical developmental period of adolescence presents community workers with an opportunity to intervene and guide the development of these youth, building upon resiliency factors, such as areas of individual mastery and empowerment and participation within the community. Aboriginal youth with a history of maltreatment present a special case for community workers. These youth have been subjected to intense acculturation pressures that do not exist for other adolescent populations, which create unique problems during their transition to adulthood. In order to intervene in the most effective manner, it is necessary to understand the psychological and physiological developmental processes that are unfolding in the adolescent brain. We discuss adolescent development in general and among Aboriginal adolescents, in particular. We present ways to support both groups through these challenging periods that are empirically-based and supported by research.